O direito de propriedade: (análise sob a ótica de sua convivência com a função social) - Zakka, Rogério Marcus (2007)
The transistion of the modern society, in which the capitalist countries had adopted the Liberal State, for the society contemporary, where it invigorates the Welfare State mark, a new vision of the right, that has its premise in the human being, not more under a optics of the individual, but as integrant of the society. In this direction, it is that a social function of the right is recognized, to demand a new reading of the institutes of the civil law, in which if it includes disciplines it of the Right of Property. The Constitution of Mexico of 1917 and the Constitution of Weimar of 1919 are the first ones to foresee the principle of the social function, establishing duties to be taken care of for the proprietors, so that the property takes care of to a social function. Currently, the principle of the social function is present, also, in our legal system, as well as the guarantee of the property right remains consecrated, between us, as right basic of the citizen. The coexistence of the guarantee of the right of property and the principle of the social function of the property estimates, to one alone time, the intervention of the state so that the property fulfills its function social and to protect the property right. The present dissertation has for objective the study of the coexistence of the principle of the social function of the property with the property right. It is intended, therefore, to interpret the content of the principle of the social function of the property and to determine the new profile of the property right